2021
DOI: 10.3390/en14082185
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic Bioethanol from Industrial Eucalyptus globulus Bark Residues Using Kraft Pulping as a Pretreatment

Abstract: The pulp and paper industry faces an emerging challenge for valorising wastes and side-streams generated according to the biorefinery concept. Eucalyptus globulus bark, an abundant industrial residue in the Portuguese pulp and paper sector, has a high potential to be converted into biobased products instead of being burned. This work aimed to evaluate the ethanol production from E. globulus bark previously submitted to kraft pulping through separate hydrolysis and fermentation (SHF) configuration. Fed-batch en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…As expectable, xylose contribution to ethanol production was not remarkable since pentose sugars are not easily metabolized. Amândio et al [ 35 ] also reported slight xylose consumption by Ethanol Red ® . In the present work, the maximum concentration of glycerol, 0.677 ± 0.005 g/L, was achieved at 13 h, showing a minor decrease after that.…”
Section: Resultsmentioning
confidence: 99%
“…As expectable, xylose contribution to ethanol production was not remarkable since pentose sugars are not easily metabolized. Amândio et al [ 35 ] also reported slight xylose consumption by Ethanol Red ® . In the present work, the maximum concentration of glycerol, 0.677 ± 0.005 g/L, was achieved at 13 h, showing a minor decrease after that.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is known as diauxic effect, consisting in glucose preference when the fermentation broth contains both glucose and xylose. Higher rate of xylose consumption was observed only after full consumption of glucose [30]. Arabinose and xylose exhaustion were detected only after 24 h, but certainly it might be occurred significantly earlier given its consumption profile.…”
Section: Microbial Bioprocess Of Liquid Streams From Subcritical Wate...mentioning
confidence: 89%
“…Regarding bark, the use of a pretreatment step has been extensively studied [18]. The main pretreatments employed were kraft pulping and hot water extraction (HWE) [26,40,41,131,132]. Besides these two processes, steam explosion (SE) was also extensively applied to sawdust [48,50,59,[133][134][135].…”
Section: Lignocellulosic Biomass Pretreatmentsmentioning
confidence: 99%
“…Regarding the conversion of E. globulus bark into bioethanol, studies are scarce (Table 1). Recently, Amândio et al [132] assessed the bioethanol production from E. globulus bark previously submitted to kraft pulping through SHF configuration. The maximum ethanol concentration of 50.8 ± 0.5 g L −1 was achieved using Ethanol Red ® (Saccharomyces cerevisiae yeast) after 20.5 h, corresponding to the productivity of 2.48 ± 0.02 g L −1 h −1 and 81.0 ± 0.6% of the theoretical yield (0.511 g ethanol g sugars −1 ) [132].…”
Section: Bioethanol Production From Barkmentioning
confidence: 99%